2020
DOI: 10.1017/s2040174420000513
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of early overfeeding and food restriction during puberty on cardiac remodeling in adult rats

Abstract: Nutritional disorders during the perinatal period cause cardiometabolic dysfunction, which is observable in the early overfeeding (EO) experimental model. Therefore, severe caloric restriction has the potential of affecting homeostasis through the same epigenetic mechanisms, and its effects need elucidation. This work aims to determine the impact of food restriction (FR) during puberty in early overfed obese and non-obese animals in adult life. Three days after delivery (PN3), Wistar rats were separated into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The intense gene transcription and protein translation in this phase results in a particular susceptibility to epigenetic modifications, leading to the later development of cardiovascular diseases. 12,13 We have previously reported that 30-day-old rats submitted to food restriction presented cardiomyocyte hypertrophy and interstitial and perivascular fibrosis accompanied by higher expression of both AT1 and AT2 receptors, 19 suggesting that the RAS may participate in pathological cardiac adjustments within the puberty programming window. In addition, our group previously showed that the treatment with Ang-(1-7) during the gestational period was able to attenuate the increase of blood pressure in the adult offspring of SHR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The intense gene transcription and protein translation in this phase results in a particular susceptibility to epigenetic modifications, leading to the later development of cardiovascular diseases. 12,13 We have previously reported that 30-day-old rats submitted to food restriction presented cardiomyocyte hypertrophy and interstitial and perivascular fibrosis accompanied by higher expression of both AT1 and AT2 receptors, 19 suggesting that the RAS may participate in pathological cardiac adjustments within the puberty programming window. In addition, our group previously showed that the treatment with Ang-(1-7) during the gestational period was able to attenuate the increase of blood pressure in the adult offspring of SHR.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Our group has previously shown that the treatment with an ACE2 activator (diminazene aceturate) or Ang-(1-7) during the gestational period of pregnant spontaneously hypertensive rats (SHRs) attenuated the development of hypertension and cardiac remodeling in the adult offspring. 18 We have reported that young rats (30-day-old) submitted to food restriction developed cardiac remodeling and increased the cardiac expression of AT1 and AT2 receptors, 19 suggesting that the RAS may participate in pathological cardiac adjustments within the prepuberty programming window. Therefore, there is no evidence that the treatment with Ang-(1-7) in the prepuberty can promote cardioprotection in adulthood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Nutritional disorders, such as overnutrition or undernutrition during phenotypic plasticity periods program to obesity, diabetes, and cardiovascular disorders. [4][5][6] Epidemiological and experimental studies have demonstrated that a high-fat (HF) diet induces overweight/obesity, hyperphagia, insulin resistance, glucose intolerance, hepatic dysfunctions, and other disturbances. [7][8][9][10] Specifically, HF intake during the puberty induces abnormalities in reproductive function, adiposity, and impairment of hippocampal-dependent memory associated with enhanced hippocampal inflammation later in life in male rats.…”
Section: Introductionmentioning
confidence: 99%